Design and experiment of a hydraulic lifting wind field test platform for crop protection UAS - Zhang, Songchao; Gu, Wei; Qiu, Baijing; Xue, Xinyu; Zhou, Lixin (International Journal of Agricultural and Biological Engineering, 2021)
As a new type of crop protection machine, the crop protection unmanned aerial system (CPUAS) is developing rapidly in China. The wind field generated by the rotor has a great influence on the deposition and penetration of spraying droplets. The purpose of this study was to develop a reliable and stable test platform that could be used for wind field test of CPUAS, and to carry out the downwash experiments on the platform to obtain the downwash distribution law of a CPUAS Z-3N (100 kg level, Nanjing Research Institute on Simulation Technique, Nanjing, China). The tests showed that the performances of the developed platform could meet the expected design requirements. The platform operated stably and reliably during the downwash experiments of Z-3N, which indicated it could be applied for CPUASs of 100 kg level and below. The vibration characteristics of the platform with different heights (2.0 m, 3.0 m, 5.0 m, 7.0 m, 10.0 m) were obtained through modal analysis, which could effectively guide avoiding the resonance for stable and reliable operation during the experiments with the tested CPUAS Z-3N. A ring-radial method was designed combined with the platform for the downwash measurement. The experimental results showed that the downwash distribution of Z-3N was not symmetrical; the downwash wind speed decreased with the increase of the radial distance while the changing trend was not consistent as the height increased. Moreover, the area with high wind speed was mainly within 3.0 m of the radial distance, and the maximum value was 11.37 m/s. The study provided a new way for wind field test of CPUASs and would provide some references for better utilization of wind field during the CPUAS spraying. Keywords: crop protection, unmanned aircraft system, wind field, test platform, vibration modal, aerial spraying DOI: 10.25165/j.ijabe.20211404.6262 Citation: Zhang S C, Gu W, Qiu B J, Xue X Y, Zhou L X. Design and experiment of a hydraulic lifting wind field test platform for crop protection UAS. Int J Agric & Biol Eng, 2021; 14(4): 166–174.